Induction of Protective Immunity against Toxoplasmosis in BALB/c Mice Vaccinated with Toxoplasma gondii Rhoptry-1 - Sonaimuthu, Parthasarathy; Ching, Xiao T.; Fong, Mun Y.; Kalyanasundaram, Ramaswamy; Lau, Yee L. (Frontiers in Microbiology, 2016)
Toxoplasma gondii is the causative agent for toxoplasmosis. The rhoptry protein 1 (ROP1) is secreted by rhoptry, an apical secretory organelle of the parasite. ROP1 plays an important role in host cell invasion. In this study, the efficacy of ROP1 as a vaccine candidate against toxoplasmosis was evaluated through intramuscular or subcutaneous injection of BALB/c mice followed by immunological characterization (humoral- and cellular-mediated) and lethal challenge against virulent T. gondii RH strain in BALB/c mice. Briefly, a recombinant DNA plasmid (pVAX1-GFP-ROP1) was expressed in CHO cells while expression of recombinant ROP1 protein (rROP1) was carried out in Escherichia coli expression system. Immunization study involved injection of the recombinant pVAX1-ROP1 and purified rROP1 into different group of mice. Empty vector and PBS served as two different types of negative controls. Results obtained demonstrated that ROP1 is an immunogenic antigen that induced humoral immune response whereby detection of a protein band with expected size of 43 kDa was observed against vaccinated mice sera through western blot analysis. ROP1 antigen was shown to elicit cellular-mediated immunity as well whereby stimulated splenocytes with total lysate antigen (TLA) and rROP1 from pVAX1-ROP1 and rROP1-immunized mice respectively readily proliferated and secreted large amount of IFN-γ (712±28.1 pg/ml and 1457±31.19 pg/ml respectively) and relatively low IL-4 level (94±14.5 pg/ml and 186±14.17 pg/ml respectively). These phenomena suggested that Th1-favored immunity was being induced. Vaccination with ROP1 antigen was able to provide partial protection in the vaccinated mice against lethal challenge with virulent RH strain of tachyzoites. These findings proposed that the ROP1 antigen is a potential candidate for the development of vaccine against toxoplasmosis.